Distributed Autonomous Robotic Systems The 14th International Symposium - Correll, Nikolaus; Schwager, Mac; Otte, Michael (Springer Proceedings in Advanced Robotics,, 2019)
This volume of the SPAR series brings the proceedings of the fourteen edition of the DARS symposium on Distributed Autonomous Robotic Systems, whose proceedings have been published within SPAR since the past edition. This symposium took place in Boulder, CO from October 15th to 17th, 2018. The volume edited by Nikolaus Correll and Mac Schwager contains 36 scientific contributions cutting across planning, control, design, perception, networking, and optimization, all united through the common thread of distributed robotic systems.